Restricted reproductive rights and risky sexual behaviour: How political disenfranchisement relates to women's sense of control, well-being and sexual health. (February 2018) - Msetfi, Rachel; Jay, Sarah; O'Donnell, Aisling T; Kearns, Michelle; Kinsella, Elaine L; McMahon, Jennifer; Muldoon, Orla T; Naughton, Catherine; Creaven, Ann-Marie
Few studies have investigated the role of disenfranchisement and denial of agency in women's sexual health. To address this, a cross-sectional study of disenfranchisement, control (general and reproductive control) and health was conducted in Ireland, where abortion is severely restricted. Multiple mediation models ( N = 513 women) indicated that general but not reproductive control mediates the association between disenfranchisement and psychological well-being. Additionally, serial mediation shows disenfranchisement is associated with lower sense of control, which is linked to poorer well-being and risky sexual behaviour. Disenfranchisement arising from socio-political contexts may have important implications for women's sexual health.